2004
DOI: 10.1016/j.ymthe.2004.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Transgene Expression from Plasmid DNA Gene Therapy Vectors Is Negatively Affected by CpG Dinucleotides

Abstract: CpG-reduced, CMV-based plasmid DNA constructs encoding human alpha-galactosidase A and factor IX were injected into C57Bl/6, BALB/c, and CD1 mice using hydrodynamics-based delivery of plasmid DNA (pDNA), and gene expression was monitored for 6 months. Linearized and supercoiled pDNAs were compared for their abilities to support long-term expression and to generate immune responses to the transgene product. In all mouse strains supercoiled CpG-reduced pDNA encoding alpha-galactosidase A and factor IX generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
2
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 51 publications
1
90
2
2
Order By: Relevance
“…Firstgeneration plasmid vectors, such as the pGL3 plasmid, used in our experiments contain unmethylated C-phosphate-G (CpG) and other sequences of bacterial origin, which have been shown to trigger premature silencing of the episomal plasmid DNA. Advancements in plasmid gene transfer technologies such as CpGreduced 32 or 'minicircle' 33,34 gene transfer constructs have been shown to express for months after non-viral gene transfer. With non-viral gene transfer to the salivary glands now a practicable reality, perfecting the plasmid vector to allow gene expression for clinically-relevant durations, perhaps 6 months between boosters, is a paramount translational goal.…”
Section: Discussionmentioning
confidence: 99%
“…Firstgeneration plasmid vectors, such as the pGL3 plasmid, used in our experiments contain unmethylated C-phosphate-G (CpG) and other sequences of bacterial origin, which have been shown to trigger premature silencing of the episomal plasmid DNA. Advancements in plasmid gene transfer technologies such as CpGreduced 32 or 'minicircle' 33,34 gene transfer constructs have been shown to express for months after non-viral gene transfer. With non-viral gene transfer to the salivary glands now a practicable reality, perfecting the plasmid vector to allow gene expression for clinically-relevant durations, perhaps 6 months between boosters, is a paramount translational goal.…”
Section: Discussionmentioning
confidence: 99%
“…35 In similar reports, 36,37 it was verified that CpG dinucleotides could negatively affect transgene expression from pDNA in vivo, even with linearization of the transgene expression plasmid before hydrodynamic injection. Finally, other groups have reported the negative effect of CpG methylation in vitro, 38 and recently the extensive methylation of CpG islands of a CMV promoter-driven adenoviral vector following delivery into the muscles of mice was shown, with methylation levels similar to our results.…”
Section: Persistent Expression In Vivo From S/mar Plasmidmentioning
confidence: 84%
“…However, the low and transient nature of the induction of inflammatory cytokines after the injection of naked pDNA by the hydrodynamics-based procedure suggests that sustained gene expression from the pGZB vector is due not only to a reduction of the inflammatory response, but also to other mechanisms that have so far not been investigated. 33 Transcriptional repression of endogenous genes is often associated with a higher frequency of methylated cytosine residues in the 5 0 flanking region of the genes: promoter or enhancer. 34,35 Moreover, CpG methylation has been reported to be associated with the absence of integrated viral gene expression 36 and it has been suggested that de novo methylation of foreign DNA represents a cellular defense mechanism against the transcription of a foreign gene.…”
Section: Discussionmentioning
confidence: 99%